2003
DOI: 10.1248/cpb.51.857
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial Activity of Prenylated Xanthones from the Fruits of Garcinia mangostana

Abstract: Prenylated xanthones, isolated from the fruit hulls and the edible arils and seeds of Garcinia mangostana, were tested for their antituberculosis potential. Alpha- and beta-mangostins and garcinone B exhibited strong inhibitory effect against Mycobacterium tuberculosis with the minimum inhibitory concentration (MIC) value of 6.25 microg/ml. Tri- and tetra-oxygenated xanthones with di-C5 units or with a C5 and a modified C5 groups are essential for high activities. Substitution in the A and C rings has been sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
128
0
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(137 citation statements)
references
References 20 publications
2
128
0
7
Order By: Relevance
“…In contrast, the same study reported only low inhibitory activity towards Escherichia coli, Klebsiella spp and Proteus spp. More recent studies have reported Mycobacterium tuberculosis 45 , S. aureus (including MRSA) 46 , Propionibacterium acnes and S. epidermidis 47 inhibitory activities of mangosteen xanthones. Numerous studies have also documented the anticancer effects of xanthones isolated from G. mangostana fruit pericarp.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the same study reported only low inhibitory activity towards Escherichia coli, Klebsiella spp and Proteus spp. More recent studies have reported Mycobacterium tuberculosis 45 , S. aureus (including MRSA) 46 , Propionibacterium acnes and S. epidermidis 47 inhibitory activities of mangosteen xanthones. Numerous studies have also documented the anticancer effects of xanthones isolated from G. mangostana fruit pericarp.…”
Section: Discussionmentioning
confidence: 99%
“…This family is known to be a rich source of polycyclic polyprenylated acylphloroglucinols (PPAPs) with a large spectrum of biological activities (Cuesta-Rubio et al, 2005;Marti et al, 2009). Besides, some plants of Clusiaceae family have their pharmacological properties associated with the presence of xanthone derivatives, which has antioxidant and anticarcinogenic activities (Sundaram et al, 1983;Chen et al, 1996;Iinuma et al, 1996;Suksamrarn et al, 2003;Ee et al, 2008;Chomnawang et al, 2009;Hung et al, 2009).…”
Section: Platonia Insignismentioning
confidence: 99%
“…Among the Clusiaceae family, Platonia insignis Mart., commonly known as "bacuri," is a timber and fruit native species of the Brazilian Amazon (Sundaram et al, 1983;Chen et al, 1996;Iinuma et al, 1996;Suksamrarn et al, 2003;Ee et al, 2008;Chomnawang et al, 2009;Hung et al, 2009). The bacuri fruit has a thick-skin, and is 7-15 cm long and 5-15 cm in diameter, weighing 200-1000 g, containing a large quantity of resins.…”
Section: Platonia Insignismentioning
confidence: 99%
“…It is one of the most popular fruits named 'the queen of fruits'. It has been known to be of good medicinal value and is traditionally used in folk medicines for treatment of abdominal pain, diarrhea, dysentery, infected wounds, suppuration, chronic ulcer, leucorrhoea and gonorrhoea 4 . Phytochemical studies showed that hulls of this plant contained various secondary metabolites, such as tannins, triterpenes, anthocyanins, xanthones, polysaccharides, phenolic compounds, vitamins B1, B2 and C, and other bioactive substances 5 .…”
Section: Garcinia Mangostana Linn (Mangosteen) Familymentioning
confidence: 99%